Three-Dimensional Magnetic Resonance Imaging Reveals the Relationship Between the Control of Vertigo and Decreases in Endolymphatic Hydrops After Endolymphatic Sac Drainage With Steroids for Meniere's Disease - Ito, Taeko; Inui, Hiroshi; Miyasaka, Toshiteru; Shiozaki, Tomoyuki; Matsuyama, Shohei; Yamanaka, Toshiaki; Kichikawa, Kimihiko; Takeda, Noriaki; Kitahara, Tadashi (Frontiers in Neurology, 2019)
Meniere's disease is a common disease, with an incidence of 15-50 per 100,000, that presents with recurrent vertigo and cochlear symptoms. The pathology of Meniere’s disease was first reported to involve endolymphatic hydrops in 1938. The endolymphatic sac is thought to maintain the hydrostatic pressure and endolymph homeostasis for the inner ear. As a surgical treatment for intractable Meniere’s disease, endolymphatic sac drainage with intraendolymphatic sac application of large doses of steroids is performed to control the endolymphatic hydrops and preserve or improve inner ear function. In the present study, to observe the effect of this surgery, we calculated the endolymphatic space size using 3-Tesla magnetic resonance imaging (MRI) 4 hours after intravenous injection of gadolinium enhancement at two time points: just before surgery and two years after. To reveal the condition of the endolymphatic space, we constructed three-dimensional MR images semi-automatically and fused the three-dimensional images of the total fluid space of inner ear and the endolymphatic space. After fusing the images, we calculated the volume of the total fluid space and endolymphatic space. Two years after surgery, 16 of 20 patients (80.0%) showed relief from vertigo/dizziness and reductions in the ratio of the volume of the endolymphatic size to the total fluid space of inner ear. Endolymphatic sac drainage with intraendolymphatic sac application of large doses of steroids could control vertigo/dizziness and decrease the endolymphatic hydrops. These results indicate that endolymphatic sac drainage is a good surgical option for patients with intractable Meniere’s disease. In addition, volumetric measurement of inner ear volume could be useful for confirming the effect of treatments on Meniere’s disease.